ANALYSIS OF THE IMPACT OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT IN IMPROVING JOB SATISFACTION IN MSMEs - Muh. Husriadi; Fari Aus; Nada Kusuma; Citra Ayu Ningsih (Adisam Publisher, 2024)
Inclusive, collaborative and transparent organizational culture has a vital role in improving performance employees at Micro, Small, and Medium Enterprises (MSMEs) in Kendari City. Although thus, the implementation of this culture is still meet obstacles in creating an optimal work environment. This study aims to identify characteristics of organizational culture that influence performance employees in MSMEs Kendari City. With qualitative research methods, data was obtained through interview in-depth with employees and MSMEs owners. The results of the study show that an inclusive, collaborative and transparent organizational culture has a positive impact on performance. employee past improvement involvement, synergy team, and trust. Core values such as integrity, innovation, and service customer participate plays an important role in strengthening the foundation of organizational culture as well increase productivity employees. These finding underlines importance implementation of a supportive organizational culture as a sustainable strategy for performance in MSMEs